KONSEP PENDIDIKAN KELUARGA DALAM ISLAM (Studi Analisis Kitab Tarbiyah Al-Aula>d fi> Al-Isla>m Karya Abdullah Nashih Ulwan) - Nur Hayati (Universitas Hasyim Asy'ari (UNHASY) Tebuireng Jombang, 2020)
Education is a process of repair, strengthening, and improvement of all human abilities and potential. Family is the first education, parents have the authority to educate their children. The educational results the child will determine next education. In this case the problem that needs attention in future education will be the issue of family education. To deliver children to be successful people in the world and the hereafter, parents must provide basic education for their children and Islamic education materials to equip their children in the future. Then it needs a concept of education that leads to the process of instill the values of education, especially religion, that is through more comprehensive education which is the responsibility of parents in the family. The focus of this research is 1) how the concept of family education in Islam, 2) how the concept of family education in the book of Tarbiyah Al-Aula>d fi> Al-Isla>m. The purpose of this study is 1) to find out the concept of family education in Islam, 2) to analyze the concept of family education in the book of Tarbiyah Al-Aula>d fi> Al-Isla>m. This study uses a type of library reseach or library research that is research carried out using literature (literature) in the form of books, notes and reports on the results of research and previous research. The approach used in this study is a descriptive analysis approach. Descriptive analysis is the data collected is in the form of words, images, and not numbers. This the researchers tried to explain the concept of family education in the book of Tarbiyah Al-Aula>d fi> Al-Isla>m. From the results of the analysis obtained the concept of family education in the book of Tarbiyah Al-Aula>d fi> Al-Isla>m, that is: faith, moral and psychological education. The becoming of faith education is to open the lives of children with the sentence Tauhid Laa ilaha illallah, teach halal and haram problems after he has understanding, order him to worship at the age of seven, educate him to love the Prophet, his family and love to read the Qur'an. Moral education that is educating children morals improves their souls, rectifies deviations. While in psychiatric education that is Growing faith in children since the beginning of its growth. familiarize children to get along with others, simple attitude, confident and courageous attitude to life. This research is expected to be useful for families, especially parents' responsibility for their children's education.